World anthropologies : disciplinary transformations within systems of power - Ribeiro, Gustavo Lins; Escobar, Arturo, 1951- (Wenner-Gren international series., 2006)
Aims to assess the diversity of relations between regional or national anthropologies and a contested, power-laden Western discourse. Critically examining the international dissemination of anthropology within and across national power fields, this book provides the outline for a veritable world anthropologies project.